Future Control and Automation Proceedings of the 2nd International Conference on Future Control and Automation (ICFCA 2012) - Volume 1 - Deng, Wei.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This volume Future Control and Automation- Volume 1 includes best papers selected from 2012 2nd International Conference on Future Control and Automation (ICFCA 2012) held on July 1-2, 2012, Changsha, China. Future control and automation is the use of control systems and information technologies to reduce the need for human work in the production of goods and services. This volume can be divided into five sessions on the basis of the classification of manuscripts considered, which is listed as follows: Identification and Control, Navigation, Guidance and Sensor, Simulation Technology, Future Telecommunications and Control.
From the Contents: Monitoring and Analyzing for Overflowing Status of Hotan River in Summer Season Based on EOS/MODIS Data -- Research on Landscape Characteristics of Tibet Landuse -- A New Evaluation Model to Evaluation of Water Resources Renewability Ability -- Experimental Study on Sand Intercepting Process of Arbor Vegetation in Interlaced Zone of Desert and Oasis in Region of Arakan -- Accelerating 3D Ocean Model Development by using GPU Computing -- Land cover Change Detection in Oasis of Hotan River Basin in Northwestern China -- Seamless Visualization of Global Multi-Resolution DEM Based on Block DQG Model -- Variational Data Assimilation of Land Surface Model with MODIS Data -- Shape Recognition in Support of Simplification of Buildings.
Keywords: Robotics; Automation; Control engineering; Electrical engineering; Robotics and Automation; Control and Systems Theory; Electrical Engineering